2022
DOI: 10.3390/socsci11050199
|View full text |Cite
|
Sign up to set email alerts
|

Prostitution and Deservingness in Times of Pandemic: State (Non) Protection of Sex Workers in Spain

Abstract: During the COVID-19 health crisis, the Spanish Government launched a series of urgent measures to protect the population from its economic effects. At first, it seemed that sex workers would have access to this protection, given that, technically, their access to the star measure, the IMV (anagram in Spanish for Ingreso Mínimo Vital) (minimum living income), was explicitly expressed. However, in the end, this group was excluded as the final text specified that only those deemed to be victims of gender violence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Related to the loss of income, food insecurity during the pandemic was a recurrent theme across the global literature (Aantjes et al, 2023;Burgos & Del Pino, 2021;Callander et al, 2022;Gonzalez & Garrido, 2022;Hassan et al, 2023;Kavanagh et al, 2021;Lamontagne et al, 2022;Leyva-Moral et al, 2023;Mantell et al, 2021;Moura et al, 2022;Moyo et al, 2022;Museva et al, 2021;Pearson et al, 2022;Pollard et al, 2021;Rogers et al, 2021;Shankar et al, 2022;Silva & dos Santos Câmara 2020;Tan et al, 2021aTan et al, , 2021bWang et al, 2022). Kavanagh et al (2021) found that participants in Kenya who relied on transactional sex for income were 5.3% more likely than those who did not to report difficulty obtaining food in the previous month and 18.3% more likely to report being worried their household would not have enough food.…”
Section: Food Insecuritymentioning
confidence: 99%
See 3 more Smart Citations
“…Related to the loss of income, food insecurity during the pandemic was a recurrent theme across the global literature (Aantjes et al, 2023;Burgos & Del Pino, 2021;Callander et al, 2022;Gonzalez & Garrido, 2022;Hassan et al, 2023;Kavanagh et al, 2021;Lamontagne et al, 2022;Leyva-Moral et al, 2023;Mantell et al, 2021;Moura et al, 2022;Moyo et al, 2022;Museva et al, 2021;Pearson et al, 2022;Pollard et al, 2021;Rogers et al, 2021;Shankar et al, 2022;Silva & dos Santos Câmara 2020;Tan et al, 2021aTan et al, , 2021bWang et al, 2022). Kavanagh et al (2021) found that participants in Kenya who relied on transactional sex for income were 5.3% more likely than those who did not to report difficulty obtaining food in the previous month and 18.3% more likely to report being worried their household would not have enough food.…”
Section: Food Insecuritymentioning
confidence: 99%
“…Sex workers across almost all studies reported needing to resume sex work while lockdown restrictions were still in place due to financial pressures. In addition to struggling to pay for housing and food, many were already in debt and could not afford to lose more (Burgos & Del Pino, 2021); sex workers with children had additional costs associated with education and online schooling such as wi-fi, laptops and tablets to enable their children to learn remotely (Dziuban et al, 2021;Hassan et al, 2023;Laikram & Pathak, 2021;Shekhar, 2023); migrant workers often had families in their home countries they sent money to (Burgos & Del Pino, 2021;Gonzalez & Garrido, 2022;Kahambing, 2021); and migrant workers who traveled to their homes during lockdown and then returned had costs associated with quarantine on their arrival back to the countries they worked in (Dziuban et al, 2021). In a study from Thailand, Laikram and Pathak (2021) found that those who identified as "other" gender as opposed to cisgender male or female were the most affected economically, for a number of reasons-they typically experienced lower demand and lower pay even pre-pandemic; they faced tough competition among themselves; and they often had more expenses such as beauty surgery, make-up, and expensive attire and accessories.…”
Section: Economic Need To Resume Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The government focuses on data collection and well-localized infectious diseases, while the public interpret it as the lack of responsiveness by the local government, resulting in the violence by the public. As a result, additional problems arise (González & Garrido, 2022).…”
Section: Tobirin Abdul Aziz Nasihuddin and Kadar Pamujimentioning
confidence: 99%